2015
DOI: 10.3892/mmr.2015.3574
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively spliced products lacking exon 12 dominate the expression of fragile X mental retardation 1 gene in human tissues

Abstract: Fragile X mental retardation 1 gene (FMR1) expression is associated with fragile X syndrome (FXS) and exhibits several splicing products. However, the proportion of spliced isoforms that are expressed in different tissues remains unclear. In the present study, long-chain reverse transcription-polymerase chain reaction with a T cloning-sequencing method was conducted in order to analyze the entire coding region of the FMR1 gene in human tissues. In particular, FXS-associated tissues were analyzed, including the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…We used the rat homolog of human isoform 17 (rat isoform X3), a highly abundant isoform. 10,11 We demonstrate correction of several key autism-related behaviors and encephalogram (EEG) patterns in the Fmr1 KO rat, further establishing the efficacy of AAV-mediated expression of FMRP as a potential long-lasting therapeutic treatment for FXS.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…We used the rat homolog of human isoform 17 (rat isoform X3), a highly abundant isoform. 10,11 We demonstrate correction of several key autism-related behaviors and encephalogram (EEG) patterns in the Fmr1 KO rat, further establishing the efficacy of AAV-mediated expression of FMRP as a potential long-lasting therapeutic treatment for FXS.…”
Section: Introductionmentioning
confidence: 69%
“…Alternative splicing of the FMR1 gene is complex and results in at least 15 mRNA isoforms expressed in human and rodent cells and tissues. [7][8][9][10][11] Based on mRNA expression experiments, isoform 1 is now known to be a relatively minor isoform. Isoforms lacking exon 12 (which contains part of the sequence for the RNA-binding K homology domain KH2) appear to constitute most of the FMR1 mRNAs in human brain tissue samples.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the antibodies we used to IP endogenous FMRP were specific for the C-terminus to avoid cross-reaction with FXR1P and FXR2P. A very small percentage of spliced isoforms of FMRP result from the exclusion of exon 14, perhaps 4-6%236,237 and these minor forms are nuclear since exon 14 encodes the nuclear export signal. Edouard Khandjian has proposed an interesting role for these nuclear FMRP isoforms in Cajal bodies238 ,…”
mentioning
confidence: 99%
“…This was based on the assumption that the full-length isoform 1 was a major variant. However, this turned out to be incorrect as FMR1 mRNA isoform expression surveys conducted in human [67,68] and mouse blood cells and brain tissue [69] have indicated that isoform 1 is expressed at lower levels compared to several other splice variants. For example, isoforms lacking exon 12 appear to be among the most abundant [68].…”
Section: The Pathway From Preclinical Experimentation To a Clinicamentioning
confidence: 99%
“…However, this turned out to be incorrect as FMR1 mRNA isoform expression surveys conducted in human [67,68] and mouse blood cells and brain tissue [69] have indicated that isoform 1 is expressed at lower levels compared to several other splice variants. For example, isoforms lacking exon 12 appear to be among the most abundant [68]. Moreover, deletion of exon 14 has been found to affect the subcellular localization of FMRP [67,70], and in premutation carriers all isoforms are elevated with isoforms 10 and 10b showing the largest increase; the consequences of differential elevations in Fmr1 isoforms remain unknown [9].…”
Section: The Pathway From Preclinical Experimentation To a Clinicamentioning
confidence: 99%